The occurrence of Crepidobothrium sp. (Cestoda, Proteocephalidae) in Bothrops moojeni (Hoge) (Serpentes, Viperidae) - Silva, Reinaldo José da [UNESP] (2001)
The occurrence of Crepidobothrium sp.(Cestoda, Proteocephalidae) in the intestine of Bothrops moojeni (Hoge,1965)(Serpentes, Viperidae) is reported. The host snake was rescued from the fauna in Porto Primavera dam, Mato Grosso do Sul State, Brazil. The snake died in captivity on July 13,1999. At necropsy, 28 tapeworms were found in the snake intestine. The analysis of specimens morphology allowed the conclusion that they belong to the Crepidobothrium (Monticelli, 1900) genus. It was not possible to determine the Crepidobothrium species due to the lack of the gravid proglottids. This is the first report of B. moojeni as a host of cestodes.